2017
DOI: 10.1038/s41598-017-11512-6
|View full text |Cite|
|
Sign up to set email alerts
|

Polyphenols journey through blood-brain barrier towards neuronal protection

Abstract: Age-related complications such as neurodegenerative disorders are increasing and remain cureless. The possibility of altering the progression or the development of these multifactorial diseases through diet is an emerging and attractive approach with increasing experimental support. We examined the potential of known bioavailable phenolic sulfates, arising from colonic metabolism of berries, to influence hallmarks of neurodegenerative processes. In silico predictions and in vitro transport studies across blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
232
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(241 citation statements)
references
References 77 publications
9
232
0
Order By: Relevance
“…In this context, the ability of LnHS (and pure compounds therefrom) to cross the blood brain barrier (BBB) is aimed to be promptly pursued. This is in line with several recent evidences which highlight the ability of dietary polyphenols, and their known physiologically relevant metabolites, to enter the brain endothelium, cross the BBB and to impact brain health and cognition [61][62][63]. The BBB-crossing feature in phenylamides and lignanamides could be improved by the intrinsic amide function occurrence.…”
Section: Resultssupporting
confidence: 88%
“…In this context, the ability of LnHS (and pure compounds therefrom) to cross the blood brain barrier (BBB) is aimed to be promptly pursued. This is in line with several recent evidences which highlight the ability of dietary polyphenols, and their known physiologically relevant metabolites, to enter the brain endothelium, cross the BBB and to impact brain health and cognition [61][62][63]. The BBB-crossing feature in phenylamides and lignanamides could be improved by the intrinsic amide function occurrence.…”
Section: Resultssupporting
confidence: 88%
“…Microbial metabolites derived from dietary lignans, a class of polyphenols, like equol and enterolactone, passively cross both the gut and BBB barriers and show protective ability against inflammation in microglia [128]. A recent study demonstrates that microbial polyphenol metabolites could be transported across the BBB endothelium [129]. In vitro experiments showed that some polyphenols' metabolites cross BBB by transmembrane diffusion and their lipophilicity can determine greater or minor uptake [130].…”
Section: Bioactivity Of Polyphenols and Gut Microbiota Interplaymentioning
confidence: 99%
“…Oxidative stress environment is believed to be one of the main factors of this age-associated brain disfunction, induced by reduced endogenous antioxidant levels and increased reactive oxygen species (ROS) production, linked to a chronic low-grade neuroinflammatory status [2][3][4]. Dietary antioxidants, with special relevance of polyphenols due to their availability in the diet, have been shown to limit some effects of aging, particularly brain aging, due to their capacity to cross the blood-brain barrier [5][6][7]. Among polyphenol-rich products, the green tea extracts (made from Camellia sinensis leaves) have drawn attention due to its large consumption worldwide as an infusion.…”
Section: Introductionmentioning
confidence: 99%